A Novel Reverse Phase High-Performance Liquid Chromatography Method Development and Validation for Determination and Estimation of Niraparib and Abiraterone Drug with its Bulk Form and Tablet Formulation (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: Measurement which is simultaneous of Niraparib and Abiraterone in/to bulk and pharmaceutical dosageform with forced degradation investigations, a straightforward, stability-indicating, and reliable reverseliquid reverse phase high-performance liquid chromatography approach has been devised and validated.Materials and Methods: The Sunfire C18 Column, measuring 100Å, 5 μm, 3 mm, and 250 mm, was employedas the stationary liquid for the separation. The mobile phase consisted of CH3OH and 0.1% trifluoroacetic acidin a 60:40 ratio, maintained at a flow velocity of 0.9 mL/min, with a maximum wavelength of 220 nm at a tempof 30°C. Niraparib and Abiraterone were shown to have average retention durations of 4.378 and 3.350 min,respectively. Results: Six injections of the Standard were used to study the system suitability characteristics,and the findings fell considerably below the accepted table threshold (limit of